Plasma surface modification coupled with thermal and step-over distance effects on significant fracture improvement of adhesively-bonded metal-CFRTP dissimilar materials. (8th February 2023) - Qiao, Yao; Shin, Yongsoon; Pallaka, Madhusudhan R.; Nickerson, Ethan K.; Merkel, Daniel R.; Seffens, Robert J.; Ortiz, Angel; Ramos, Jose L.; Simmons, Kevin L.
Abstract: This work proposes an approach to improve the interfacial bonding between carbon-fiber-reinforced thermoplastic polymers (CFRTP) and thermoset adhesive by using the surface modification with the combination of air plasma, thermal, and step-over distance ( i.e., treatment pattern) effects in a single plasma surface treatment system. Thanks to the proper heating which causes the exposure of carbon fibers on the CFRTP surface, both polymer matrix and these exposed carbon fibers can have improved bonding with adhesive due to air plasma treatment. By conducting the Double Cantilever Beam (DCB) tests performed on adhesively-bonded AA5052/CFRP-PA66 dissimilar joints, it was shown in this work that the average Mode I specific fracture energy can be improved up to about 180% compared to non-treated counterparts. The foregoing improvement can be further increased by considering the step-over distance of the surface treatment, which triggers the tortuous damage path in the failure process of adhesively-bonded structures. By manipulating this treatment parameter, often overlooked in the literature, and other parameters ( i.e., treatment speed, nozzle tip-to-surface distance, etc.) investigated in this study, the average Mode I specific fracture energy of adhesively-bonded AA5052/CFRP-PA66 dissimilar joints can be improved reaching up to about 410% compared to non-treatment counterparts. Graphical abstract: